Alignment and ergativity in new Indo-Aryan Languages - Verbeke, Saartje (Empirical approaches to language typology, 2013)
"The book provides an overview of the alignment patterns found in modern Indo-Aryan languages. The analysis of the patterns of case marking and agreement leads to a balanced view on the concept of ergativity and evaluates its value for typological linguistics. The book offers an extensive discussion of previous approaches to ergativity. It analyzes four Indo-Aryan languages--Asamiya, Nepali, Rajasthani and Kashmiri--on the basis of text corpora. Examples from other Indo-Aryan languages are also adduced. The book is a thorough synchronic study of alignment patterns in Indo-Aryan languages"--Provided by publisher.